Maximum density in the Moina macrocopa culture able to produce parthenogenesis in female offspring. (February 2019) - Mubarak, A S; Jusadi, D; Junior, M Z; Suprayudi, M A
Abstract: Population density in the culture of Moina macrocopa affects the production of offspring per parent. Female parthenogenesis is able to produce a high population density. Information on the M. macrocopa culture densities for inoculant provision is not yet available. This study aims to examine the density of the culture of M. macrocopa against the production of offspring per parent and the percentage of female parthenogenesis offspring production. The treatments in this study were differentiated parent densities ranging from 20 ind/ L to 330 ind/L and each with three replications. During the culture, M. macrocopa was fed with a rice bran suspension. The results of this study indicated that M. macrocopa was cultured using rice bran suspension feed in the parent density of 66 ind/L, which produced offspring per parent (8.56 to 13.01) equal to the parent density of 20 ind/L, whereas all of the females were parthenogenesis females. M. macrocopa was cultured with a mother density of 330 ind/L, which produced the highest female sexual ephippia and male offspring in the first until the third birthing round.